2020
DOI: 10.1101/2020.03.02.973404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ongoing exposure to peritoneal dialysis fluid alters resident peritoneal macrophage phenotype and activation propensity

Abstract: Peritoneal dialysis (PD) is a more continuous alternative to haemodialysis, for patients with chronic kidney disease, with considerable initial benefits for survival, patient independence and healthcare cost. However, longterm PD is associated with significant pathology, negating the positive effects over haemodialysis. Importantly, peritonitis and activation of macrophages is closely associated with disease progression and treatment failure. However, recent advances in macrophage biology suggest opposite func… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…88,89 However, uncontrolled complement activation also contributes to hyperinflammation, cell injury, immunothrombosis, and multiorgan failure during COVID-19 infection. 90 In addition, monocytes/ macrophages from patients with ESKD have increased expression and activity of the macrophage scavenger receptors SR-A and CD36, [91][92][93] but decreased inducible nitric-oxide synthase expression 94 and phagocytic capability, e.g., of peritoneal macrophages in chronic PD and PD-induced peritonitis 95,96 and potentially also in alveolar macrophages in the context of pulmonary infections. ESKD reduces the cell number and cytotoxicity of natural killer (NK) cells in association with downregulation and modulation of ligand expression for activating receptors on NK cells.…”
Section: Impaired Function Of Innate Immunitymentioning
confidence: 99%
“…88,89 However, uncontrolled complement activation also contributes to hyperinflammation, cell injury, immunothrombosis, and multiorgan failure during COVID-19 infection. 90 In addition, monocytes/ macrophages from patients with ESKD have increased expression and activity of the macrophage scavenger receptors SR-A and CD36, [91][92][93] but decreased inducible nitric-oxide synthase expression 94 and phagocytic capability, e.g., of peritoneal macrophages in chronic PD and PD-induced peritonitis 95,96 and potentially also in alveolar macrophages in the context of pulmonary infections. ESKD reduces the cell number and cytotoxicity of natural killer (NK) cells in association with downregulation and modulation of ligand expression for activating receptors on NK cells.…”
Section: Impaired Function Of Innate Immunitymentioning
confidence: 99%
“…A possible explanation for this is that the unit of PD duration in our study was years, not months. Tara et al 15 suggested that alterations in tissueresident macrophages may render long-term PD patients sensitive to developing peritonitis, which consequently puts them at a higher risk of Encapsulating Peritoneal Sclerosis(EPS), an urgent indication to discontinue PD. Because of improved worldwide survival rates, the number of patients with long PD duration is increasing.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Technique failure-related peritonitis may be associated with higher overall mortality for those on dialysis for ≥ 3 years when compared to those on it for < 3 years. This may be attributed to the in uence of long-term PD duration on peritoneum function 15 , which highlights the need for enhanced surveillance of long-term PD peritonitis patients, especially those with a PD duration longer than 3 years. To the best of our knowledge, this is the rst study to investigate the effect of PDRP history on technique failure and post-dialysis survival rates.…”
Section: Survival Analysismentioning
confidence: 99%
“…We’d also like to thank Sister Trish Smith from the Royal Manchester Children’s Hospital for the provision of Physioneal 40, Dr John Grainger (University of Manchester, UK) for the provision of the Cx3cr1 CreER :R26-eyfp mice as well as Prof. Judith E. Allen (University of Manchester, UK) for use of her Home Office animal licence and critical appraisal of the work. This manuscript was deposited as a pre-print version on BioRxiv prior to peer review ( 90 ).…”
Section: Acknowledgmentsmentioning
confidence: 99%